Therapies from Fucoidan; Multifunctional Marine Polymers - Janet Helen Fitton (Marine Drugs, 2011)
Published research on fucoidans increased three fold between 2000 and 2010. These algal derived marine carbohydrate polymers present numerous valuable bioactivities. This review discusses the role for fucoidan in the control of acute and chronic inflammation via selectin blockade, enzyme inhibition and inhibiting the complement cascade. The recent data on toxicology and uptake of fucoidan is detailed together with a discussion on the comparative activities of fractions of fucoidan from different sources. Recent in vivo, in vitro and clinical research related to diverse clinical needs is discussed. Targets include osteoarthritis, kidney and liver disease, neglected infectious diseases, hemopoietic stem cell modulation, protection from radiation damage and treatments for snake envenomation. In recent years, the production of well characterized reproducible fucoidan fractions on a commercial scale has become possible making therapies from fucoidan a realizable goal.